Light on yoga : the classic guide to yoga from the world's foremost authority - Iyengar, B. K. S (London: HarperCollins, 2010)
Light On Yoga is a classic text on the philosophy and practice of Yoga.Light On Yoga is a definitive guide about Yoga, a rigorous discipline for attaining physical, mental, and spiritual well-being. It is aimed at beginners as well as advanced practitioners of Yoga. The book begins a foreword by Yehudi Menhuin, a famous violinist and a friend of the author. It is divided into three parts. The first part contains an introduction to Yoga, tracing its historical origin to ancient India. The second part is dedicated to yogasanas, bandhas, and kriyas. It covers numerous asanas or poses in great detail. Each asana is illustrated by a photograph.
Keywords: Yoga